GAMBARAN PENGETAHUAN IBU HAMIL TENTANG KURANG ENERGI KRONIS - Idawati Ambohamsah; Farmin Arfan; Siti Aulia Farhana (J-KESMAS: Jurnal Kesehatan Masyarakat, 2025)
Maternal nutritional status before and during pregnancy is very important for fetal growth. If the mother's nutrition is good during pregnancy, it is likely that the baby will be born healthy. Lack of nutritional intake, such as Chronic Energy Deficiency (CED), can have a negative impact on the health of the mother and fetus. Therefore, it is important to pay attention to nutrition from the beginning of pregnancy until the beginning of the baby's life. Chronic Energy Deficiency (CED) in pregnant women can cause risks and complications for the mother, including: the mother not gaining weight normally, anemia, bleeding, and contracting infectious diseases. The World Health Organization (WHO) states that the prevalence of CED in pregnancy globally is 35% -75%. WHO also notes that 40% of maternal deaths in developing countries are related to KEK. Based on 2018 Riskesdas data, West Sulawesi Province has a prevalence of CED in pregnant women of 17.53%. The three districts with the highest percentage of KEK are Central Mamuju District (41.33%), Mamasa District (31.84%), and Polewali Mandar District (25.8%). This study employs a descriptive methodology with questionnaire-based data gathering procedures to pregnant women in the Massenga Community Health Center working area. The aim is to identify and describe the level of knowledge of pregnant women about CED. Data was examined using factors like age, education, employment, and mother's parity. Research shows that the level of knowledge of pregnant women about CED varies. The majority of respondents had good knowledge (70.0%), sufficient knowledge (23.3%), some still had low knowledge (6.7%). Factors that influence pregnant women's knowledge about KEK include education level and employment. Higher education and certain occupations tend to increase mothers' knowledge of SEZs.